Empowering Small Businesses: My Transformative Internship Experience Interned at Triva Digital - Silamkoti, Akhil Vishwesh (ATLAS SkillTech University, 2025)
Digital marketing and website development are essential for businesses worldwide. Today, almost every company, regardless of size, needs a strong online presence to stay competitive. This need has driven the growth of digital marketing agencies all over the world. Companies look for experts to manage their social media, create engaging content, and develop user-friendly websites. The need for services related to digital marketing has been rising as additional businesses realize that an effective online strategy is key to their success. Globally, this industry is growing rapidly, with businesses investing more in online advertising, SEO, social media management, and other digital strategies.
Project Report on Empowering Small Businesses: My Transformative Internship Experience Interned at Triva Digital (2023-2025) Under the Guidance of Prof. Tapish Panwar
Keywords: Digital marketing; marketing; website development; social media; engaging content; user-friendly websites; SEO; advertising; digital strategies